Teens' blog accounts of the role of adults in youth alcohol consumption - Pettigrew, Simone; Pescud, M.; Jarvis, W.; Webb, D. (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this paper is to discuss the role of parents and other adults in preventing and facilitating teen binge drinking.Design/methodology/approach – Teens’ discussions on internet websites were accessed to examine their opinions of their alcohol-related interactions with adults.Findings – The results show that in the context of a western society such as Australia, the role of adults in endorsing a culture of excessive alcohol consumption may be considerable.Practical implications – Social marketing campaigns are needed to sensitise adults to this situation and outline strategies that can be used by adults to reduce negative impacts and enhance their potential to reduce alcohol consumption among young people.Originality/value – Previous research into teenagers’ alcohol consumption behaviours has focused on self-reports obtained via surveys or focus groups. Such data collection processes are likely to be subject to considerable social desirability bias. The present study demonstrates that the internet can constitute a valuable alternative source of data relating to young people’s engagement in unhealthybehaviours and the factors impacting their decisions to enact these behaviours.